Aplikasi Green Financial Literacy dalam Pemanfaatan Pembiayaan Hijau untuk Teknologi Daur Ulang dan Pengomposan di Kalangan UMKM Kuliner Kota Maumere - Wanda Maria; Imelda Wisang; Marselinus Bosko (Lembaga Pengembangan Kinerja Dosen, 2025)
Culinary MSMEs in the city of Maumere produce significant food and packaging waste that can cause environmental pollution such as soil and water as well as problems for the sustainability of culinary MSMEs if not properly managed. Awareness of the importance of sustainable business practices is increasing on a national scale, but culinary MSMEs in the city of Maumere are not optimal. Green technology innovation and the adoption of environmentally friendly practices are strategies that can increase competitiveness while supporting business sustainability. That way, the environmental sustainability aspect not only reduces the negative impact on the ecosystem, but also creates new business opportunities through the development of environmentally friendly products and services. The purpose of this study was to determine the influence of green financial literacy on the use of green financing among culinary MSMEs in Maumere City, and the use of green financing affects the adoption of recycling and composting technology among culinary MSMEs in Maumere City. This study uses a qualitative approach to understand the use of green financing for recycling and composting technology among culinary MSMEs in Maumere city. The findings in this study through SWOT analysis are that the implementation of green financial literacy in the culinary MSME sector in Maumere has a significant foundation of strength and opportunities. However, its success is highly dependent on literacy capacity building, policy support, and access to green financing that is easily accessible to small business actors. An integrated strategy between the government, financial institutions, and MSME actors will be the key to realizing culinary MSMEs that are not only competitive, but also environmentally sustainable.